Hubungan Iklim Komunikasi Organisasi terhadap Peningkatan Motivasi Kerja Pegawai di STKIP Muhammadiyah Rappang Kabupaten Sidenreng Rappang - Hj Chaerati (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract This research aimed to determine the climate in organizational communication in STKIP Muhammadiyah Rappang in Sidenreng Rappang District. Also to determine the level of employee motivation and to investigate the relationship between the climate in organizational communication and the levels of employee motivation. The results showed that the organizational communication in STKIP Muhammadiyah Rappang in Sidenreng Rappang District was at high category. This confirmed that the leaders’ organizational communication through subjective communication approach, empathy and openmindedness to subordinates will contribute to employees’ motivation. The level of employee motivation was also at high category. This gave an appreciation and desire of the leaders that through the implementation of effective interpersonal communication the higher employees’ motivation through encouragement approach, curiosity and ability/confidence with the leaders the higher the motivation obtained later. The leaders’ organizational communication had a strong correllation with the level of employees’ motivation in STKIP Muhammadiyah Rappang in Sidenreng Rappang District. Keywords: Organizational Communication, Work Motivation